STRATEGI DIGITAL MARKETING PADA TOKO ONLINE SHOP NYEMIL CEMIL TULUNGAGUNG DALAM MENINGKATKAN VOLUME PENJUALAN - Lutfi Nur Azizah; Siswahyudianto Siswahyudianto (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This research is motivated by a digital marketing strategy to increase sales volume. As marketing is a trend that is shifting from conventional (offline) to digital (online). With this digital marketing concept, business people feel helped and can market their products from anywhere and anytime via the internet. This study aims to find out what digital marketing strategy is used by the Nyemil Cemil Tulungagung Online Shop in increasing sales volume. The method used is a qualitative research approach. The results showed that (1) The application of digital marketing at the Nyemil Cemil Online Shop was successfully implemented so that it could increase its sales volume. (2) The 7P Marketing Mix (Product, Price, Place, Promotion, People, Process, Physical Evidence) was successfully implemented so as to provide increased sales (3) The constraints faced were also given solutions to be able to provide a system that could be applied by the Nyemil Cemil Online Shop Shop Tulungagung